ตัวประกอบการกระแทกตามตำแหน่งต่างๆ บนคานสะพาน - ปานนท์ ลาชโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
Generally, bridges are designed assuming constant truck loads slowly travelling on the decks. The static analysis is applicable and the effects of bridge dynamics are taken into account using the impact factor. Based on the past studies, the design codes recommend the impact factor in term of span length or bridge’s natural frequency. However, those studies considered the impact effect only at bridge’s mid-span. Consequently, the bridge design at other locations might be unsafe. This research studies the impact factor at different locations along the bridge girders. The relationships between impact factor and relevant parameters such as span length, bridge’s natural frequency, velocity and truck’s weight are considered and the effect of initial condition of a vehicle is investigated. The mathematical model representing the vehicle-bridge interaction is formulated. The computer simulations under various conditions of passing vehicles including vehicle speed, span length and surface roughness are conducted. The obtained results indicate that the impact factor with considering initial condition is always higher than that without considering initial condition. The obtained impact factors seem to have significant correlation with the bridge’s natural frequency as recommended by Canadian code (OHBCD). In addition, the maximum values of impact factor are found at other bridge positions, especially around bridge’s supports, rather than at bridge mid-span. Therefore, it is necessary that the impact formula needs to be improved in order to guarantee the bridge safety.